Biodiversity of Cellulolytic Bacteria Isolated from the Solid Wastes of Agar Seaweed Processing Industry - Ifah Munifah; Titi Candra Sunarti; Hari Eko Irianto; Anja Meryandini (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2015)
Agar is polysaccharide extracted from the seaweed Gracilaria sp. It is commonly used for food, medical, pharmaceutical and biotechnology industries. The red seaweed Gracilaria verrucosa is the most common material used for the extraction of agar, processed into sheet and powder. A total of 7169 tons solid waste is produced from the agar industry in Indonesia which can further result in 4301.4 tons per year of cellulose. However, solid wastes from agar seaweed processing industry have not been managed and used optimally, and therefore seaweed solid wastes can be used as one of alternative source of cellulose and cellulolytic bacteria. In this research, we reported the isolation of cellulose-producing bacteria from seaweed processing industry wastes using specific media 1 % LIA (Limbah Industri Agar, waste of seaweed processing industry). Sequencing and subsequent phylogenetic analysis of the 16S rRNA genes amplified from the obtained 7 isolates identified them as Serratia marcescens, Chryseobacterium indovlogenes, Bacillus pumilus, Bacillus cereus, Strenatrophomonas maltophila, and Pseudomonas aeruginosa.